A comparative study in machining of AISI D2 steel using textured and non-textured coated carbide tool at the flank face. (December 2018) - Rajbongshi, Sanjib Kr; Annebushan Singh, Meinam; Kumar Sarma, Deba
Highlights: Surface texturing at the flank face of coated carbide tool is created using μ-EDM. Dry turning of AISI D2 steel is performed using non-textured and textured tool. Responses flank wear and surface roughness is compared using non-textured and textured tool. Flank wear and surface roughness is found less using textured tool. White layer thickness and micro hardness is reduced at the machined surfaces using textured tool. Abstract: Surface texturing over a cutting tool in machining is a process where a tribological alteration occurs in the tool-chip interfaces. The present work analyzes the influence of surface texturing of the coated carbide tool on the flank face during machining. Linear microgrooves are prepared on the flank face of the coated carbide tool orthogonal to the cutting edge. The experiments are conducted in the dry turning of AISI D2 steel (45 HRC) using both textured and non-textured tool. Total eight experiments are conducted considering three factors (cutting speed, feed, and depth of cut) having two levels each. The responses of flank wear and surface roughness are studied for comparison of the performance of textured tool with the non-textured tool. In all the cases, flank wear of the textured tool is found to be less as compared to the non-textured tool. Other hand, except few in most of the cases, surface roughness is found to be lower with textured tool as compared to non-textured tool. The analysis of machined samples revealed that texturing helps in reducing the formation of white layer thickness and micro-hardness as compared to the non-textured tool. The decrease in white layer thickness at the machined surface is supported by the decrease in temperature at the tool-chip interface using the textured tool as compared to the non-textured tool. Thus, texturing in flank face of coated carbide tool improves the machinability in terms of flank wear and tool life.